2019
DOI: 10.3389/fpsyt.2018.00781
|View full text |Cite
|
Sign up to set email alerts
|

Bone Status in Obese, Non-diabetic, Antipsychotic-Treated Patients, and Effects of the Glucagon-Like Peptide-1 Receptor Agonist Exenatide on Bone Turnover Markers and Bone Mineral Density

Abstract: Background: Low bone mineral density (BMD) may constitute an underestimated comorbidity in schizophrenia patients undergoing long-term antipsychotic treatment. Glucagon-like peptide 1 (GLP-1) receptor agonists are antidiabetic drugs, which may also affect bone turnover.Methods: In planned secondary analyses of a 3 months, double-blind, randomized, placebo-controlled trial (n = 45), we explored effects of the GLP-1 receptor agonist exenatide 2 mg once-weekly (n = 23), or placebo (n = 22) on bone turnover marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In non-diabetic, overweight men, GLP-1 infusion seems to reduce the extent of bone resorption in a similar way to GIP [787]. However, in obese, non-diabetic patients under anti-psychotic drugs, exenatide failed to modify significantly the pattern of bone remodeling [870]. In contrast, liraglutide was capable of enhancing bone formation in obese weight-reducing women while having no effects on bone resorption [871].…”
Section: Glp-1 Effects On Bonementioning
confidence: 99%
“…In non-diabetic, overweight men, GLP-1 infusion seems to reduce the extent of bone resorption in a similar way to GIP [787]. However, in obese, non-diabetic patients under anti-psychotic drugs, exenatide failed to modify significantly the pattern of bone remodeling [870]. In contrast, liraglutide was capable of enhancing bone formation in obese weight-reducing women while having no effects on bone resorption [871].…”
Section: Glp-1 Effects On Bonementioning
confidence: 99%
“…However, to date, only few clinical studies have shown the association between bile acid metabolism and BMD. Moreover, the underlying mechanisms remain unknown (9,10).…”
Section: ' Introductionmentioning
confidence: 99%
“…( 42 ) Furthermore, in a trial involving obese people without diabetes who were on antipsychotic treatment, a 3‐month exposure to exenatide did not lead to any changes in BMD in the lumbar spine, femoral neck, or total hip. ( 43 )…”
Section: Effects Of Incretins On Bone Healthmentioning
confidence: 99%
“…However, no changes were observed in these measurements in the liraglutide treatment group. (40) Overall, the studies suggest that GLP-1 RAs, particularly liraglutide (39,40,44,45) and exenatide, (41)(42)(43)46,47) may have varying effects on bone metabolism and BMD in different populations, including T2D people and obese people, although the effect of the drugs is generally neutral. The impact on bone health appears to be influenced by factors such as weight loss, genetic mutations, and the presence of diabetes.…”
Section: Human Studiesmentioning
confidence: 99%